21SSD: a new public 21-cm EoR database. Issue Volume 12:Issue S333(2017) (8th May 2018) - Eames, Evan; Semelin, Benoît
Abstract: With current efforts inching closer to detecting the 21-cm signal from the Epoch of Reionization (EoR), proper preparation will require publicly available simulated models of the various forms the signal could take. In this work we present a database of such models, available at21ssd.obspm.fr . The models are created with a fully-coupled radiative hydrodynamic simulation (LICORICE), and are created at high resolution (1024 3 ). We also begin to analyse and explore the possible 21-cm EoR signals (with Power Spectra and Pixel Distribution Functions), and study the effects of thermal noise on our ability to recover the signal out to high redshifts. Finally, we begin to explore the concepts of 'distance' between different models, which represents a crucial step towards optimising parameter space sampling, training neural networks, and finally extracting parameter values from observations.